Repeated evolution of eye loss in Mexican cavefish: Evidence of similar developmental mechanisms in independently evolved populations. Issue 7 (2nd July 2020) - Sifuentes‐Romero, Itzel; Ferrufino, Estephany; Thakur, Sunishka; Laboissonniere, Lauren A.; Solomon, Michael; Smith, Courtney L.; Keene, Alex C.; Trimarchi, Jeffrey M.; Kowalko, Johanna E.
Abstract: Evolution in similar environments often leads to convergence of behavioral and anatomical traits. A classic example of convergent trait evolution is the reduced traits that characterize many cave animals: reduction or loss of pigmentation and eyes. While these traits have evolved many times, relatively little is known about whether these traits repeatedly evolve through the same or different molecular and developmental mechanisms. The small freshwater fish, Astyanax mexicanus, provides an opportunity to investigate the repeated evolution of cave traits. A. mexicanus exists as two forms, a sighted, surface‐dwelling form and at least 29 populations of a blind, cave‐dwelling form that initially develops eyes that subsequently degenerate. We compared eye morphology and the expression of eye regulatory genes in developing surface fish and two independently evolved cavefish populations, Pachón and Molino. We found that many of the previously described molecular and morphological alterations that occur during eye development in Pachón cavefish are also found in Molino cavefish. However, for many of these traits, the Molino cavefish have a less severe phenotype than Pachón cavefish. Further, cave–cave hybrid fish have larger eyes and lenses during early development compared with fish from either parental population, suggesting that some different changes underlie eye loss in these two populations. Together, these data support the hypothesis that these two cavefish populations evolved eye loss independently, yet through some of the same developmental and molecular mechanisms. Abstract : Astyanax mexicanus from two distant cavefish populations evolved eye regression through some similar developmental and molecular mechanisms. HIGHLIGHTS: Shared and distinct genetic and developmental pathways characterize two independently evolved cavefish populations.